Theoretical and Experimental Investigation of the Dissipated and Stored Energy Ratio in Iron under Quasi-Static and Cyclic Loading - Plekhov, O.; Uvarov, S.; Naimark, O. (Проблемы прочности, 2008)
The problem of energy storing (cold work accumulation) in metals was intensively investigated both theoretically and experimentally during all last century but a general theoretical conception of the process was not created. This work is devoted to an experimental investigation of energy dissipation in metals under plastic deformation and to the development of a thermodynamic model to study the cold work accumulation under plastic deformation and failure. The proposed model is based on a statistical description of collective properties of mesoscopic defects and on dividing the plastic deformation into two parts (dissipative and structural). The structural plastic strain was considered as an independent thermodynamic variable that allowed us to determine the thermodynamic potential of the system. The derived constitutive relations were applied for numerical simulation of tensile and cyclic tests. The numerical results demonstrate a good agreement with experimental data.